The right to free legal aid in the criminal proceedings of BiH or RS - Buha, Milijana Lj (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2020)
The Institute for Free Legal Assistance in Criminal Procedure ensures that the right to adequate defense is provided to socially vulnerable subjects in criminal proceedings. The users of free legal aid in the criminal procedure are suspects, ie the accused, the injured party, and victims of the criminal offense of trafficking in human beings and domestic violence. The core of the free legal aid institute is to avoid discrimination on the part of citizens on a property basis, and to ensure the right to defend in criminal proceedings even to individuals with a poor financial situation. Entities of the right to free legal aid in criminal proceedings do not have to meet the same conditions in order to be beneficiaries of this right. Depending on whether the poor property status of users of the right to free legal aid in criminal proceedings is set as an imperative requirement or not, we can talk about conditional and unconditional free legal aid for some criminal actors. The paper examines the thesis that in criminal proceedings some of the subjects of the criminal procedure enjoy the right to free legal aid unconditionally, in the sense that they do not have to prove that they are in a bad condition, they are already in the inability to pay the costs of the criminal proceedings.